The Transformation of Object Representations of Student’s Visual on Geometry Problem Solving - Feny Rita Fiantika; I Ketut Budayasa; Agung Lukito (Pancaran Pendidikan, 2018)
Geometry is one of many ways to understand the real world, since we can find Geometry concept in real life daily applications. Through some nets of a cube dices, the researcher would like to explore the transformation of object representation. How is the 5th grade elementary school student being able to transform an object representation?  Actually it is a process which using the principles of transformation to describe an object with language, pictures or gestures. The subjects of this study were the concepts of students visual in 5th grade of elementary school. The researcher conducted a learning style test to the 5th grade students and gave a geometry problem to them; these can be used to indicate the profile the transformation of object representation on visual subject. The result of the research showed that subjects using a frame of reference, changing the point of view from 2 dimensions to 3 dimensions object, it was changing the shape of 2D to 3D by their imagination and also moving the objects.